Sobralia turrialbina (Orchidaceae: Sobralieae): Long Cultivated and Now Described - Dressler, Robert L. (2016)
Sobralia turrialbina is described and illustrated from Costa Rica. The new species is compared with the morphologically similar S. chrysostoma, from which can be distinguished by the leaves restricted to the terminal third of the stem, the floral bracts twice longer, the flowers dusty pink or pale rose, and the lip with no keels, provided with a hazelnut-brown gorge and the apical margin finely striped with rose-purple. Notes on species distribution, habitat and ecology, and etymology are provided